Evaluating virtually: a closer look at university supervisor/preservice teacher relationships during asynchronous virtual evaluations - Callanan, Vanessa L. (My University, 2025)
Preservice teaching experiences are the final stage of perspective teachers' education and often, supervisors at the university level are charged with completing their evaluations. During this stage, it is critical that university supervisors provide insightful input and feedback regarding the performances of the preservice educators, as through this process, burgeoning educators may improve their pedagogy, refine their classroom management skills, and gain valuable insights in the field. While this practice has existed for decades, the emergence and prevalence of new technologies has allowed for a different type of evaluation: asynchronous virtual observations. This study expands on the body of research that exists on the training of university supervisors to adapt these asynchronous virtual evaluations, and explores best practices, rapport-building, and development of valuable feedback strategies when using online video software. As a result of this study, three insights emerged regarding the use of asynchronous virtual evaluations: the importance of initial and sustained communication, the use of constructive, specific feedback strategies, and the perceived inauthenticity of recorded classroom lessons. Findings from this study indicate that while virtual evaluations tools offer a great deal of flexibility for schools of education, there is much refinement that needs to be made to fully maximize the benefits for preservice educators and university supervisors. Furthermore, when viewed through the lens of a dual-dialogic theoretical framework, the findings of this study suggest that additional steps be taken to enhance the communicative potential of university supervisors, including the use of cohorts to help increase understanding, compassion, and empathy. This dissertation concludes with a set of implications, suggestions, and areas in which this topic may be studied further as virtual evaluations continue to grow in use and scope.
Keywords: Virtual teacher evaluations; Preservice teacher supervision; Rapport; Feedback